2011 Design, Automation &Amp; Test in Europe 2011
DOI: 10.1109/date.2011.5763298
|View full text |Cite
|
Sign up to set email alerts
|

HypoEnergy. Hybrid supercapacitor-battery power-supply optimization for Energy efficiency

Abstract: Abstract-This paper presents HypoEnergy, a framework for extending the hybrid battery-supercapacitor power supply lifetime. HypoEnergy combines high energy density and reliable workload supportability of an electrochemical battery with high power density and high number of recharge cycles of supercapacitors. The lifetime optimizations consider nonlinear battery characteristics and supercapacitors' charging overhead. HypoEnergy-KI studies the hybrid supply lifetime optimization for a preemptively known workload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Prior work has explored hybrid battery-ultracapacitor power sources to support burst currents in larger electronic systems [34] and to improve battery efficiency [32,33]. The latest ultra-capacitors have the potential to meet our requirements for energy capacity, peak current, and form factor with negligible energy losses due to leakage.…”
Section: Power Sourcementioning
confidence: 99%
“…Prior work has explored hybrid battery-ultracapacitor power sources to support burst currents in larger electronic systems [34] and to improve battery efficiency [32,33]. The latest ultra-capacitors have the potential to meet our requirements for energy capacity, peak current, and form factor with negligible energy losses due to leakage.…”
Section: Power Sourcementioning
confidence: 99%
“…Recently a hybrid battery-supercapacitor power-supply system has been proposed in which the hybrid source's charge/discharge policy is made based upon the load profile and supply's state. The work includes a novel algorithm to maximize the supply system's lifetime [3]. A number of limited earlier studies have already shown the benefits of a hybrid supercapacitor and solar energy generation system in optimizing system's efficiency and dynamic response time, in particular for transient loads with a low duty cycle and also for pulsed loads in sensor networks [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…For the example, we considered the workload scenarios of Figure 2, which are essentially based on the iPhone battery current measurements in [18,22]. The tasks considered in the scenarios include airplane mode (40 mA), default mode (100 mA), working internet with 3G network (310 mA), working game application "Tap-Tap" (220 mA), working 3D game application "GTI Racing" (400 mA), working application "YouTube" with WiFi (260 mA), working application "YouTube" (350 mA), and voice phone (170 mA) [18].…”
Section: An Illustrative Examplementioning
confidence: 99%